1997
DOI: 10.1074/jbc.272.23.15028
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitory Fragment Derived from Protein Kinase Cε Prevents Enhancement of Nerve Growth Factor Responses by Ethanol and Phorbol Esters

Abstract: We have studied nerve growth factor (NGF)-induced differentiation of PC12 cells to identify PKC isozymes important for neuronal differentiation. Previous work showed that tumor-promoting phorbol esters and ethanol enhance NGF-induced mitogen-activated protein (MAP) kinase activation and neurite outgrowth by a PKC-dependent mechanism. Ethanol also increases expression of PKC␦ and PKC⑀, suggesting that one these isozymes regulates responses to NGF. To examine this possibility, we established PC12 cell lines that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 61 publications
7
95
1
1
Order By: Relevance
“…In contrast to NGF treatment, epidermal growth factor (EGF) treatment of PC12 cells induced an acute phasic activation of p42 MAPkinase which returned to baseline within 30 min ( Figure 1B). These data are in agreement with data of several other laboratories [16,21,22,34,35]. Bailie et al reported that primary cultures of hepatocytes possess binding sites for NGF, and we investigated whether NGF had a similar capability to modulate the MAP kinase cascade in these cells [26].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast to NGF treatment, epidermal growth factor (EGF) treatment of PC12 cells induced an acute phasic activation of p42 MAPkinase which returned to baseline within 30 min ( Figure 1B). These data are in agreement with data of several other laboratories [16,21,22,34,35]. Bailie et al reported that primary cultures of hepatocytes possess binding sites for NGF, and we investigated whether NGF had a similar capability to modulate the MAP kinase cascade in these cells [26].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have demonstrated that chronic elevation of plasma ethanol levels into the " 50 mM range inhibits hepatocyte proliferation\liver regeneration in i o [23,24]. Furthermore, ethanol treatment of PC12 cells has been shown to inhibit DNA synthesis and to potentiate the ability of NGF to increase neurite outgrowth, which were shown to be dependent upon signalling via the MAP kinase cascade [21,22]. Other workers examining NGF function have shown that neurite outgrowth in PC12 cells caused by treatment with this factor is dependent upon signalling via the MAP kinase cascade, which we have confirmed (data not shown) [36].…”
Section: Figure 3 Ngf Treatment Induces P21 Cip-1 Expression In Pc12 mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that overexpression of PKCε enhanced nerve growth factor (NGF)-induced phosphorylation of ERK in PC12 pheochromocytoma cells and increased NGF-induced neurite outgrowth [80]. Ceramide inhibited growth of human embryonic kidney (HEK) 293 cells by attenuating ERK activity in a PKCε-dependent manner [81].…”
Section: Pkcε and Ras/raf/mapk Signalingmentioning
confidence: 99%
“…Based on experiments with cell lines of various origin, both PKC␦ (O'Driscoll et al, 1995;Corbit et al, 1999) and PKC⑀ (Hundle et al, 1995;Fagerström et al, 1996;Hundle et al, 1997;Brodie et al, 1999;Zeidman et al, 1999) have been proposed to be the PKC isoform that positively regulates neurite outgrowth. This could suggest that these isoforms have redundant functions, but in several other cell systems PKC␦ and ⑀ have unique and sometimes opposite effects (Mischak et al, 1993;Lehel et al, 1994;Fleming et al, 1998).…”
Section: Introductionmentioning
confidence: 99%